P237 INFLUENCE OF HEART RATE ON LEFT AND RIGHT VENTRICULAR LONGITUDINAL STRAIN IN PATIENTS WITH CHRONIC HEART FAILURE. (18th May 2022) - Di Terlizzi, V; Barone, R; Manuppelli, V; Correale, M; Casavecchia, G; Goffredo, G; Pellegrino, P; Puteo, A; Ieva, R; Di Biase, M; Brunetti, N; Iacoviello, M
Abstract: Background: Myocardial deformation evaluated by two–dimensional speckle tracking echocardiography (STE) is a useful tool to evaluate both left and right ventricular function. However, there are no conclusive data about the relationship between strain measures and heart rate (HR). Aim of the Study: To analyse changes in left (LV) and right ventricular (RV) longitudinal strain associated with variations of HR in patients with and without chronic heart failure (CHF). Methods. We enrolled 45 patients. Of the 38 patients diagnosed with CHF, 21 were carrying an ICD (Group 1), and 17 an ICD with CRT (Group 2). Group 3 included 7 participants without CHF with sinus node dysfunction that were carrying a pacemaker. The frequency of atrial stimulation was increased to 90 beats/min and an echocardiogram was performed at each increase of 10 beats/min. Global LV and RV longitudinal strain (LVGLS and RVGLS, respectively) and RV free wall longitudinal strain (RVfwLS) were calculated at each HR, together with other echocardiographic parameters. Worsening or improvement of strain measures was defined as a relative change from baseline of 10%. Results: The reproducibility of strain measurements was assessed in all the images obtained at the different HRs for 19 of the study participants. A high degree of reproducibility was observed for LVGLS (ICC = 0.96; 95% CI, 0.93 – 0.97) as well as for RVGLS (ICC = 0.91; 95%CI, 0.86 – 0.94) and RVfwLS (ICC = 0.91; 95%CI, 0.85 – 0.94). When analysed as continuous variables, significant reductions in LVGLS were detected at higher HRs, whereas improvements in both RVGLS and RVfwLS were observed (left panels of the figure). Patients with worsening of LVGLS (76% overall) were more likely to present lower baseline LV function and maximum relative changes of LVGLS correlated significantly with the E/e' ratios (r = –0.56; p < 0.001). Only few patients (18% for RVGLS and 16% for RVfwLS) exhibited HR–related worsening of RV strain measures, which was associated with lower levels of baseline RV function and higher pulmonary systolic pressures. Finally, 21 (47%) and 25 (56%) of the participants responded with improvements in RVGLS and RVfwLS, respectively. Right panels of the figure show the trend of left and right measures in the different groups. Conclusions: Our findings revealed heterogeneous RV and LV responses to increases in HR. These findings might ultimately be used to optimize cardiac functionality at rest in patients diagnosed with CHF.